Comprehensive assessment of spatter material generated during selective laser melting of stainless steel. (December 2020) - Ahmed Obeidi, Muhannad; Mussatto, Andre; Groarke, Robert; Vijayaraghavan, Rajani K.; Conway, Alex; Rossi Kaschel, Frederico; McCarthy, Eanna; Clarkin, Owen; O'Connor, Robert; Brabazon, Dermot
Graphical abstract: Highlights: Spatter is predominantly large irregular aggregates containing very small satellites. Golden coloration of spatter suggests surface chemistry changes. Spatter is lighter and has substantially larger specific surface area than virgin powder. Absorption of light of spatter is improved for some wavelengths. Abstract: Laser-powder interaction and meltpool dynamics govern the physics behind the selective laser melting process. Spattering is an unavoidable phenomenon taking place during the process which results in reconstituted particles falling within the powder bed. These are known to influence the interaction between the incident laser beam and the powder. These particles can consequently have a negative effect on final part integrity and quality of recycled powder. Hence, it is crucial to assess the characteristics of spatter particles to avoid the printing of defective parts. This work reports a detailed characterisation of spatter matter generated during the selective laser melting of stainless steel. To better assess the characteristics of the spatter, the spattered material was benchmarked against the virgin powder. The results showed no significant variation between the virgin and spattered particles in terms of the bulk material crystal structure. However, the spatter particles' morphological, surface chemical, optical and physical properties assessed do differ significantly from those of the virgin powder. The results presented in this work are of significant contribution to the powder bed fusion field of additive manufacturing as they provide a unique insight to the characteristics of spatter matter generated from the processing of 316L stainless steel powder.